Doxology Thoriqoh At-Tijaniyah in Transendental Communication Perspective - Muslih, Muhammad; Muhibudin, Agus (PT. Riset Press International, 2024)
Dhikr is a form of communication between humans and God through spiritual practices in the form of dhikr. The dhikr activity that was tried by a group of Jamiyah thoriqoh Tijaniyah was to find an activity that was tried by carrying out Allah's commands and avoiding the prohibitions and getting closer to Allah by practicing Sufism according to the example of the Prophet Muhammad who was brought by a Sufi of the Tijaniyyah tribe named Sheikh Ahmad At-Tijani. The purpose of this research is to identify how the process of applying dhikr thoriqoh At-Tijaniyah is seen from a communication perspective, and to recognize the phenomenon of the dhikr ritual of thoriqoh Tijaniyah congregation in perspective communication. The method used in this study is a qualitative method, the instrument used as a method of in-depth interviews with research subjects and conducting participatory observations in Pasawah Village, Susukan Lebak District, Cirebon Regency. The results of this study prove that the process of Thoriqoh At-Tijaniyah's dhikr activity has two ways of doxologi, there are common doxology and ikhtiyari, common doxology has 3 doxology factors: general doxology, wadzifah doxology, doxology salamalah. Dhikr wadzifah is tried every Thursday afternoon and doxology salamalah is tried every Friday afternoon.